2006
DOI: 10.1111/j.1600-0404.2006.00586.x
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in the copy number of mitochondrial DNA in leukocytes of patients with mitochondrial encephalomyopathies

Abstract: In leukocytes, alteration in the copy number of mtDNA is related to the proportion of mtDNA with a point mutation or large-scale deletion, which may serve as a biomarker in the pathogenesis and disease progression of MELAS and MERRF syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 32 publications
1
51
1
Order By: Relevance
“…Recently, Folbergrová et al (2010) reported that the persistent inhibition of Complex I led to the overproduction of ROS, which could contribute to the neuronal injury in a rat model of seizures and in the patients with epileptogene s i s . I n a p r e v i o u s s t u d y , w e o b s e r v e d a significant decrease in the copy number of mtDNA in the leukocytes of patients with mitochondrial encephalomyopathies including MERRF and MELAS syndromes, respectively (Liu et al, 2006). The amplitude of change was related to the proportion of mutant mtDNA, which may serve as a biomarker in the pathogenesis and progression of the mitochondrial diseases.…”
Section: Biochemical Hallmarks In Mitochondrial Encephalomyopathiesmentioning
confidence: 98%
“…Recently, Folbergrová et al (2010) reported that the persistent inhibition of Complex I led to the overproduction of ROS, which could contribute to the neuronal injury in a rat model of seizures and in the patients with epileptogene s i s . I n a p r e v i o u s s t u d y , w e o b s e r v e d a significant decrease in the copy number of mtDNA in the leukocytes of patients with mitochondrial encephalomyopathies including MERRF and MELAS syndromes, respectively (Liu et al, 2006). The amplitude of change was related to the proportion of mutant mtDNA, which may serve as a biomarker in the pathogenesis and progression of the mitochondrial diseases.…”
Section: Biochemical Hallmarks In Mitochondrial Encephalomyopathiesmentioning
confidence: 98%
“…Therefore, the genetic alteration of mtDNA will directly impact on the function of the OXPHOS, and may ultimately cause fertility problems [3]. The copy number of mtDNA (i.e., the number of mtDNA per spermatozoon) is one of the major mitochondrial genetic features, and plays a critical role in mtDNA-mediated pathological pathways [4][5][6][7]. For example, in infertile men with abnormal sperm quality, mtDNA content was found to be significantly increased, and could serve as a marker for spermatogenic dysfunction [8].…”
Section: Introductionmentioning
confidence: 99%
“…mtDNA mutations often result in respiratory chain defects resulting in decreased ATP production, enhanced ROS and free radical production in mitochondria. Mitochondrial dysfunction or cell apoptosis result upon the decline in the copy number of mtDNA or the accumulation oxidative damage and mtDNA mutations reaches a critical point, thus, resulting in defective energy metabolism of the target tissues (Liu et al, 2006). Alteration of mtDNA copy number in affected copy numbers has been suggested play a role in the pathogenesis and progression of mitochondrial diseases (Liu et al, 2006;Park et al, 2009).…”
Section: Mitochondrial Dna Copy Number Variationsmentioning
confidence: 99%
“…Mitochondrial dysfunction or cell apoptosis result upon the decline in the copy number of mtDNA or the accumulation oxidative damage and mtDNA mutations reaches a critical point, thus, resulting in defective energy metabolism of the target tissues (Liu et al, 2006). Alteration of mtDNA copy number in affected copy numbers has been suggested play a role in the pathogenesis and progression of mitochondrial diseases (Liu et al, 2006;Park et al, 2009). Studies have documented the presence of inheritable copy number variations (CNVs) in the human genome, and copy number aberrations (CNAs), which are acquired somatic alterations, have been observed in tumor tissues (Sun et al, 2009;Zhang et al, 2010).…”
Section: Mitochondrial Dna Copy Number Variationsmentioning
confidence: 99%
See 1 more Smart Citation